Transition metal (Mn, Fe, Co, Ni)-doped graphene hybrids for electrocatalysis - Poh, Hwee Ling (2013)
The development of electrocatalysts is crucial for renewable energy applications. Metal-doped graphene hybrid materials have been explored for this purpose, however, with much focus on noble metals, which are limited by their low availability and high costs. Transition metals may serve as promising alternatives. Here, transition metal-doped graphene hybrids were synthesized by a simple and scalable method. Metal-doped graphite oxide precursors were thermally exfoliated in either hydrogen or nitrogen atmosphere; by changing exfoliation atmospheres from inert to reductive, we produced materials with different degrees of oxidation. Effects of the presence of metal nanoparticles and exfoliation atmosphere on the morphology and electrocatalytic activity of the hybrid materials were investigated using electron microscopy, energy-dispersive X-ray spectroscopy, X-ray photoelectron spectroscopy, and cyclic voltammetry. Doping of graphene with transition metal nanoparticles of the 4th period significantly influenced the electrocatalysis of compounds important in energy production and storage applications, with hybrid materials exfoliated in nitrogen atmosphere displaying superior performance over those exfoliated in hydrogen atmosphere. Moreover, nickel-doped graphene hybrids displayed outstanding electrocatalytic activities towards reduction of O2 when compared to bare graphenes. These findings may be exploited in the research field of renewable energy.